Gender Dynamics Analysis: Uncovering the Roles and Identities of Bugis-Makassar Women - Rezky Juniarsih Nur; Siti Komariah (Pusbindiklatren Bappenas, 2023)
Gender is a social construction that involves labeling men and women. This construction is no longer based solely on biological or sex differences owned by individuals. Through a strong socialization process, gender ideology is formed and internalized in society. Gender identity is a sensation that appears around the age of two, when individuals identify themselves as male or female due to biological differences. Gender role identification, on the other hand, refers to an individual’s feelings about their gender, whether as male or female, which are influenced by social, biological, and psychological variables (Nurohim 2018). But in the gender ideology that is formed, there are stereotypes or images attached to the roles of men and women. For example, women are often connoted as beings who are gentle, beautiful, emotional, and have motherly traits. On the other hand, men are often seen as strong, rational, mighty, and possessing masculine traits. Stigma and social expectations of gender roles can influence behavior, attitudes, and expectations received by individuals in society.